2020
DOI: 10.1111/jssr.12647
|View full text |Cite
|
Sign up to set email alerts
|

Diversifying the Social Scientific Study of Religion: The Next 70 Years

Abstract: Here I argue that we need to diversify the social scientific study of religion and chart a plan for how we are already and will continue to do so. At the time of the 70th anniversary of our association, I reflect on where—as an association—we have come from and where we are going. Our origin story points to an expansive vision for what would become the Society for the Scientific Study of Religion (SSSR), but unfortunately our past has also been marked by an overrepresentation of white male leadership. It was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We must find more creative ways to go beyond Christian or non-religious sensibilities and pay more attention to other types of religious needs and sensitivities. As scholars of religion, we must also search for more creative ways to diversify intellectual depictions of religious life (Ecklund 2020), which would offer better tools to both policy makers and media commentators. We must put forward more nuanced approaches to the intersection of religion in the public square, especially regarding issues of health.…”
Section: Discussionmentioning
confidence: 99%
“…We must find more creative ways to go beyond Christian or non-religious sensibilities and pay more attention to other types of religious needs and sensitivities. As scholars of religion, we must also search for more creative ways to diversify intellectual depictions of religious life (Ecklund 2020), which would offer better tools to both policy makers and media commentators. We must put forward more nuanced approaches to the intersection of religion in the public square, especially regarding issues of health.…”
Section: Discussionmentioning
confidence: 99%
“…First, by all measures, American academics are significantly less religious than the general public (Beit-Hallahmi 2015; Gross and Simmons 2009). Next, professors and graduate students from elite institutions are the least likely to hold religious identities or practice religious behaviors (Ecklund 2010;Larson and Witham 1998;Leuba 1916). Finally, social scientists are less likely to be religious than those in the natural scientists, and sociology stands out as one of the least-religious disciplines in academia (Gross and Simmons 2009;Stark and Finke 2000;Thalheimer 1973).…”
Section: Religion Status and Objectivity In The Academymentioning
confidence: 99%
“…American academics differ vastly from the general population in terms of religious affiliation and behavior (Beit-Hallahmi 2015;Ecklund 2010;Ecklund and Scheitle 2007;Gross and Simmons 2009;Larson and Witham 1998;Leuba 1916;Stark 1963). While the United States is the most religious of all industrialized nations, the American academy is remarkably distinct.…”
Section: Religion Status and Objectivity In The Academymentioning
confidence: 99%
“…However, studies that reported on the leadership of green organizations from an Islamic perspective have not yet been discussed although past researchers such as Ecklund (2020) estimated that the population of Muslims will increase and represent the majority of humans in the world by the year 2070. Therefore, the concept of green organizational leadership from Islamic perspectives should be redefined since it has never been done before.…”
Section: Green Organizational Leadershipmentioning
confidence: 99%
“…Green organizational leadership refers to the leader's ability to influence and motivate employees to perform work (Aziz et al, 2012), while prioritizing the preservation and conservation of the environment (Norton et al, 2015;Abadiyah et al, 2020). However, there has not been a study that reports on the leadership of green organizations from an Islamic perspective, although past researchers such as Ecklund (2020) estimate that the population of Muslims will increase and represent the majority of humans in the world by the year 2070. Therefore, there is a need to develop a model of green organizational leadership on the basis of Islamic concept.…”
Section: Introductionmentioning
confidence: 99%